Seed value chains for Sorghum and Millet in Mali: A state-based system in transition - Diakité, Lamissa; Sidibé, Amadou; Smale, Melinda; Grum, Mikkel (International Food Policy Research Institute, 2008)
This paper reviews the structure and performance of the sorghum and millet seed sector in Mali. The Sahel is the origin of pearl millet and sorghum, seed selection and management of these crops is embedded in local cultures, and most producers of these crops are subsistence oriented. Despite seed sector reform, no certified seed of these crops is sold in local markets and farmers prefer to rely on themselves or each other for seed. The dominant source of certified seed is the national seed service. Certified seed is multiplied by contracted farmers and seed producer groups, and supplied to farmers through farmers' associations, development organizations, and extension services. The informal sector supplies farmers with non-certified seed directly and indirectly through village grain markets. There is no consensus about whether it is lack of effective demand or supply that constrains farmer use of certified sorghum and millet seed, but researchers generally conclude that the process of certifying seed is too lengthy, some mechanism must be established for production and trade of locally-adapted landraces, and Mali's highly structured farmers' associations could play an even stronger role in testing and promoting demand for certified seed. Recommendations have included the use of small packs and seed auctions where market infrastructure is sparse, and in more commercialized areas, involvement of agro-input dealers, shopkeepers and traders. Still, estimated adoption rates for improved millet (under 10 percent of crop area) and sorghum seed (under 20 percent of crop area) could be as high as can be expected in this challenging natural environment and institutional context.